Principal component analysis applied to study of carbon steel electrochemical corrosion. (May 2015) - Gandía, J. M.; Monzón, P.; Bataller, R.; Campos, I.; Manuel Lloris, J.; Soto, J.
Abstract : Voltammetric techniques (open circuit potential, linear polarisation resistance and cyclic voltammetry) have been applied to study the corrosion of carbon steel in water. The study has been performed in aqueous solutions for pH ranging between 7 and 12 in the presence of chlorides, sulphates, carbonates, nitrites and nitrates. Principal component analysis (PCA) was performed with the cyclic voltammetric data. Values of corrosion potential and corrosion current obtained with traditional methods are compared to the conclusions arisen by the PCA. These results show the ability of PCA for the evaluation and diagnosis of corrosion processes and not only that, it leads to the possibility of using steel working electrodes as ion sensors.